1993
DOI: 10.1111/j.1438-8677.1993.tb00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection of the Leaching‐out from Membrane‐surrounded Compartments: a New Approach Explored with Cells and Tissues of Nicotiana tabacum L.

Abstract: In search of a simple method for testing the very early events of ozone damage to susceptible plants as well as complete destruction after threshold‐exceeding treatments an over‐all measurement of cell ingredients by their optical density in the UVB and UVC range was investigated. The cell particles were liberated after membrane permeabilization or after cell bursting. Uncontrolled results could be excluded. Furthermore, the results of the developed spectrophotometrical test could be, in the case of tissue sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Plant material, growing conditions, media, protoplast isolation, ozone fumigation and membrane leaching measurement with the UVS test are previously described in detail (Stadtler, 1993). Therefore only additionally needed information for the present work is listed as follows: Sabine Stiidtler and H. Ziegler…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant material, growing conditions, media, protoplast isolation, ozone fumigation and membrane leaching measurement with the UVS test are previously described in detail (Stadtler, 1993). Therefore only additionally needed information for the present work is listed as follows: Sabine Stiidtler and H. Ziegler…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that at first cytoplasmic membrane components were oxidized (Moeschlin, 1980), especially unsaturated fatty acids from lipids (Criegee, 1975) and/or thiols from proteins (Bailey, 1958;Tomlinson and Rich, 1968) leading to the loss of semipermeability. The detection of the leaching of cell ingredients by lNS was sensitive enough to also estimate the first stages of damage (Stadtler, 1993), whereas direct evidence of these reactions is difficult to obtain, because even small changes may evoke severe effects: ozone-induced oxidation of 1 % of the total cell lipids is sufficient to kill Chlorella sorokiniana (Frederick and Heath, 1975).…”
Section: Cpmentioning
confidence: 99%